2016
DOI: 10.1038/srep35615
|View full text |Cite
|
Sign up to set email alerts
|

Folylpolyglutamate synthase is a major determinant of intracellular methotrexate polyglutamates in patients with rheumatoid arthritis

Abstract: We investigated major determinants of the intracellular concentrations of methotrexate polyglutamates (MTXPGs) in patients with rheumatoid arthritis (RA). In 271 RA patients on stable oral low dose weekly pulse MTX therapy, the concentrations of MTXPGs in red blood cells (RBCs) were measured by liquid chromatography-electrospray ionization-tandem mass spectrometry. Polymerase chain reaction-restriction fragment length polymorphism analysis was performed to determine the genotypes of solute carrier family 19 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 24 publications
3
31
1
1
Order By: Relevance
“…Our results do not replicate previous findings indicating that RFC‐1 80G>A gene polymorphisms are associated with the response to MTX. Indeed, the same results were found in Yamamoto's study, which showed that there were no relationships between the RFC‐1 80G>A polymorphism and intracellular MTXPG3‐5/1–2 ratios or MTX toxicity. Furthermore, in 327 South Indian Tamil RA patients, the RFC‐1 80G>A gene polymorphism was not found to be associated with the MTX treatment response.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Our results do not replicate previous findings indicating that RFC‐1 80G>A gene polymorphisms are associated with the response to MTX. Indeed, the same results were found in Yamamoto's study, which showed that there were no relationships between the RFC‐1 80G>A polymorphism and intracellular MTXPG3‐5/1–2 ratios or MTX toxicity. Furthermore, in 327 South Indian Tamil RA patients, the RFC‐1 80G>A gene polymorphism was not found to be associated with the MTX treatment response.…”
Section: Discussionsupporting
confidence: 78%
“…26 Similarly, a study that included 127 Indian (Asia) RA patients showed that individuals with the RFC1 80 AA/GA genotype had a better response to MTX than was observed in those with the RFC1 80 GG genotype (OR, 2.2; 95%CI, 1.1-4.4; P = .03) but was not associated with ADRs. 27 The disease severity was the same in this study and ours, and the duration 18 study, which showed that there were no relationships between the RFC-1 80G>A polymorphism and intracellular MTXPG3-5/1-2 ratios or MTX toxicity. Furthermore, in 327 South Indian Tamil RA patients, the RFC-1 80G>A gene polymorphism was not found to be associated with the MTX treatment response.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations